A cross-sectional pilot study of student's proactive behavior in midwifery education: Validation of a developed questionnaire. (March 2018) - Mestdagh, Eveline; Timmermans, Olaf; Colin, Pieter J.; Van Rompaey, Bart
Abstract: Objectives: Midwifery students face major challenges in adapting quickly and effectively to different clinical settings. Proactive behavior, triggered by various individual and/or contextual antecedents, could be a significant added value to cope with these challenges. Design: A cross-sectional pilot study was conducted to investigate prognostic factors in proactive behavior in a group of midwifery students. Settings: The setting was a Belgian University College for midwifery education. Participants: All second and third year midwifery students ( n  = 156). Methods: Students were questioned regarding several prognostic factors: four personal characteristics, seven individual antecedents and three contextual antecedents that might trigger proactive behavior. A proportional odds logistic regression analyses was used to describe the association between prognostic factors and the probability to observe proactive behavior within the group. The strength of the newly developed questionnaire was tested. Results: Of all tested prognostic factors, nationality, role breadth self-efficacy, referring to the self-confidence of a midwifery-student to perform tasks that exceed expectations, and control appraisal, describing the importance attached to one's perceived control, were significantly associated with proactive behavior. The overall strength of the questionnaire was ratified. Two of the original questions were deleted, two re-formulated and for one prognostic factor the answer-options were re-formulated. Conclusions: Findings from this pilot study show that midwifery students who have a high role breadth self-efficacy and low control appraisal are more likely to show proactive behavior. Additionally, Dutch students are more likely to show proactive behavior in relation to Belgian students. The questionnaire's feasibility was examined and adjustments were made for future research in a larger study to confirm these outcomes. This study can be a support in the individual guidance of midwifery students towards proactive behavior in midwifery. Highlights: Midwifery students with high role breadth self-efficacy tend to behave proactive. Midwifery students with low control appraisal tend to behave proactive. Dutch midwifery students rather than Belgian tend to show more proactive behavior. The proactive behavior questionnaire in midwifery education is feasible.